2004
DOI: 10.1029/2004ja010419
|View full text |Cite
|
Sign up to set email alerts
|

Generation region of pulsating aurora obtained simultaneously by the FAST satellite and a Syowa‐Iceland conjugate pair of observatories

Abstract: [1] We have carried out a direct comparison of pulsating auroras observed from the ground at Syowa Station in Antarctica and on board the FAST satellite ($3100 km altitude), with reference to simultaneous data obtained by a Syowa-Iceland conjugate pair of observatories. The aurora at Syowa appeared as east-west aligned bands consisting of two different types: a poleward moving oscillation and a standing oscillation, each with a period of $6 s. Spatial and temporal variations of the downgoing high-energy (>5 ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
4
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(138 citation statements)
references
References 28 publications
(53 reference statements)
4
129
4
1
Order By: Relevance
“…For example, rapid ∼3 Hz modulations were often found to be superimposed on the slower variations (i.e., the repetition period) of the PsA [Lepine et al, 1980;Yamamoto, 1988;Sato et al, 2004]. On the other hand, the analysis of the pulsation pattern has led to a distinction between "on time" and "off time" [Scourfield and Parsons, 1971;Yamamoto, 1988].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, rapid ∼3 Hz modulations were often found to be superimposed on the slower variations (i.e., the repetition period) of the PsA [Lepine et al, 1980;Yamamoto, 1988;Sato et al, 2004]. On the other hand, the analysis of the pulsation pattern has led to a distinction between "on time" and "off time" [Scourfield and Parsons, 1971;Yamamoto, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…(3) In this event we do not have the satellite/rocket measurements in low-or medium-Earth orbit, above the ionosphere, to infer the electron precipitation spectra and their dynamic variations leading to the PsA. On the other hand, some observational evidences from the nonconjugacy of the PsAs in two hemispheres [Sato et al, 1998, 2004, Watanabe et al, 2007, and from the energytime dispersion of precipitation electrons observed by FAST satellite [Sato et al, 2002[Sato et al, , 2004, suggest that the source regions of the generation and/or modulation of the PsAs may not be located in the equatorial magnetosphere but somewhere closer to the Earth, presumably in a magnetosphere-ionosphere interface region. Satellite observations in such a region are thus very useful since they may not only provide the information on the energy spectrum of precipitating electrons responsible for the PsA, but also help to distinguish the source regions of the generation/modulation of the precipitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations